Achieving Malaysia as high income economy by leveraging niche areas: A case of Pahang State Economic Planning Unit / Rahema Bakeri - Bakeri, Rahema (2011)
Malaysia is currently in its journey towards achieving high income economy in 2020. Towards achieving high income nation, Malaysia is steadfast to strengthening niche areas which are tourism industry, ICT Industry, Halal Industry, Green Technology and Creative Industry. However, this study is only focus to Tourism Industry, ICT Industry and Halal Industry. The main objective for this research is to determine whether all three variables can contribute to the high income economy. Information is gained through questionnaires which have been distributed to 50 staffs in Pahang State Economic Planning Unit (BPEN). The regression result obtained that tourism industry and ICT Industry are showing significant relationships with high income economy. Whereas, Halal Industry shows there is no relationship with high income. From that, it can be presumed that high income economy might be achieved by strengthening the Tourism Industry and ICT Industry. Finally, the recommendations are identified to the government and to public people in order to promote all Tourism and ICT Industry